The Development of an Empathy Curriculum (Empathy in Health) for Healthcare Students Using VR Technology - Papageorgiou, Alexia; Leinweber, Julia; Böhm, Kerstin; Constantinou, Constantina; Kolokotroni, Ourania; Karpeli, Eleni; Savoulidou, Konstantina; Strimpakos, Nikos; Knais, Christiana; Horlait, Melissa; Papastamatiou, Nikos; Papadopoulou, Chrystalleni (My University, 2023)
Empathy in Health is an Erasmus + funded project, which aims to design a curriculum for empathetic skill development in healthcare practitioners and home carers based on up-to-date evidence and cutting-edge technology tools. A literature review was carried out that focused on empathy in health care using VR technology. The results of the literature review helped develop a focus group guide for the purposes of the qualitative part of the need assessment exercise. The data from the focus groups were transcribed and analysed using the methodology of content analysis. The themes that emerged from the analysis of the focus groups’ data lent themselves to three major working areas. These informed the development of the qualification framework, which in turn informed the development of the detailed curriculum. The Empathy in Health curriculum involves 21-hour classroom teaching, 3-hour Asynchronous Electronic Learning and 6-hour Directed Self Learning for graduate students or final year undergraduate students or Health Care Professionals. The curriculum covers understanding empathy and competencies necessary for empathy, understanding empathy in relationships and information exchanges in different health care contexts/environments, showing empathy in diverse environments and overcoming barriers/challenges to empathy.
Keywords: Empathy; Virtual reality; Medical students; Midwifery students; Physiotherapy students; Patient-centeredness; Burnout; Cultural diversity; Communication skills; Educational videos; Role-plays; Focus groups